Congenital Oligodendroglioma: Clinicopathologic and Molecular Assessment with Review of the Literature - Hope Richard; Kimberly Stogner-Underwood; Christine Fuller (Hindawi Limited, 2015)
Oligodendroglioma is an infiltrating glial neoplasm frequently seen in adults. Pediatric oligodendrogliomas are rare, with very few cases presenting in infancy and only rare congenital examples. In contrast to adult oligodendrogliomas, pediatric cases typically lack 1p/19q codeletion. Herein we report a case of WHO grade II oligodendroglioma diagnosed in a 7-month-old male infant. The patient initially presented at 3 months of age with symptoms suspicious for seizure. Initial workup including electroencephalography (EEG), electrocardiogram (EKG), and computed tomography (CT) of the head was negative. His symptoms persisted, and subsequent magnetic resonance imaging (MRI) performed at age of 7 months revealed a 2 cm contrast-enhancing left temporal lobe mass. The mass was excised and the microscopic appearance was that of a classic low grade oligodendroglioma composed of cells with uniformly round nuclei, perinuclear halos, delicate branching capillaries, and an absence of high grade features. Mutant specific (R132H) isocitrate dehydrogenase-1 (IDH1) immunohistochemistry was negative, and the tumor lacked detectable 1p or 19q deletions by fluorescent in situ hybridization (FISH). The onset of neurological symptoms in early infancy followed by the positive MRI findings suggests that this case represents a rare example of congenital oligodendroglioma.